ACT: An Evidence-Based Macro Framework to Examine How Communication Approaches Can Change Social Norms Around Female Genital Mutilation - Sood, Suruchi; Kostizak, Kelli; Lapsansky, Charlotte; Cronin, Carmen; Stevens, Sarah; Jubero, Mar; Kilbane, Theresa; Obregon, Rafael (Frontiers in Communication, 2020)
Female genital mutilation (FGM) is a complex harmful traditional practice associated with prevalent social norms. Yet, there is a lack of social norms focused conceptual and measurement frameworks to assess the impact of social and behavior change communication-based interventions towards ending the practice of FGM. This manuscript describes the development of an evidence-based macro framework to measure FGM behavior and social norms change over time. ACT is an acronym for the different sections of the framework: 1) Assess What People Know, Feel, and Do; 2) Ascertain Normative Factors; 3) Consider the Context, Especially Gender and Power; 4) Collect Information on Social Networks and Support; 5) Track Individual and Social Change Over Time; and 6) Triangulate All Data Analysis. ACT takes a social-ecological perspective to change and was constructed using various social norms theories, both in general and specific to FGM. Subsequently, meetings were held with social norms and FGM field experts across the world to further refine the framework. The ACT framework includes a menu of constructs, indicators, methods, and tools that can be adapted according to available resources, the local context, and research limitations. Both qualitative and participatory quantitative methods are described. Descriptions of the steps necessary to measure social norms change with regard to FGM through monitoring and evaluation are included. The ACT framework allows for change to be directly linked to the communication approaches used by interventions through attribution and contribution using indicators to measure outputs, short-term outcomes, and exposure. Triangulation is built into the ACT framework to facilitate validation, enrichment, and holistic interpretation of data, as well as creating a feedback loop. ACT is currently being validated in two countries in Africa in which FGM is practiced to different extents. Next steps are discussed.